Synthesis and Verification of a Novel Attainable Tumor Targeting Magnetic Nanoparticle - Yingxiu Chen; Jiasheng Yan (Polskie Towarzystwo Farmaceutyczne, 2023)
This study aimed to prepare a novel multifunctional magnetic nanoparticle (MNP) with a drug-loadable encapsulation and a matrix metalloproteinase (MMP) substrate-modified TAT peptide whose transmembrane ability can be activated in an MMP-rich environment, and to evaluate the uptake of this nanoparticle by cells, as well as its cytotoxicity. Nanoparticles were synthesized and modified with TAT or MMPs-TAT peptides. PC-3 cells and RWPE-1 cells were cultured with these nanoparticles at different concentrations, with or without MMP-2 pretreatment, and their uptake rate and toxicity were determined using flow cytometry and fluorescence microscopy. The nanoparticles were characterized with TEM (transmission electron microscopy) and DLS (dynamic light scattering). The diameter of these nanoparticles ranged from 194.5 ± 69.4 nm to 353.1 ± 103.9 nm, which were in the ideal range for application. The cellular uptake of MMPs-TAT-MNPs appeared similar to MNPs, but significantly increased in the presence of MMP-2 pretreatment. MMPs-TAT-MNPs had no significant cytotoxicity at the concentration of ≤25 μg/ml. MMPs-TAT-MNPs with MMP-2 substrate modified TAT peptide is successfully prepared, possess a low cytotoxicity loadable cargo and can be activated in an MMP-2 rich niche.